Asymmetric Ocean Response to Atmospheric Forcing in an Island Wake: A 35-Year High-Resolution Study - Alves, José M. R.; Tomé, Ricardo; Caldeira, Rui M. A.; Miranda, Pedro M. A. (Frontiers in Marine Science, 2021)
The present study assesses the thermal variability of the regional ocean around Madeira Island, in intraseasonal and interdecadal time scales, using a 35-year (1983–2017), 3-km horizontal resolution ocean simulation forced by a co-located atmospheric simulation, with SODA and ERA5 boundary and initial conditions, respectively. Atmosphere–ocean interactions in this region are found to be driven by the variability of two quasi-permanent tip-jets, located at the island west and east tips, especially during the summer months. The ocean response is found to be larger in the regions of higher jets speed variability, but its thermal response is highly asymmetrical. On the interdecadal time scale, a significant intensification of both jets during the analyzed period is more prominent in the east tip, but the thermal signature is mostly associated with a much reduced sea surface temperature trend near the west tip.